2006
DOI: 10.1097/01.mlg.0000195286.29613.e1
|View full text |Cite
|
Sign up to set email alerts
|

Microvessel Density in Head and Neck Squamous Cell Carcinoma Primary Tumors and Its Correlation with Clinical Staging Parameters

Abstract: Our series demonstrates that there is a strong correlation between MVD in primary tumor hot spots and tumor T-stage, which implies that tumor angiogenesis may be a factor in tumor progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 9 publications
2
16
0
1
Order By: Relevance
“…Several studies reported strong correlation between high microvessel counts and both recurrent or metastatic disease in HNSCC [6,7]. In 2005 a meta-analysis confirmed previous data about levels of VEGF and risk of lymph node metastases (1.88-fold higher risk of death at 2 years) [8].…”
Section: Results Of Preclinical Datasupporting
confidence: 74%
“…Several studies reported strong correlation between high microvessel counts and both recurrent or metastatic disease in HNSCC [6,7]. In 2005 a meta-analysis confirmed previous data about levels of VEGF and risk of lymph node metastases (1.88-fold higher risk of death at 2 years) [8].…”
Section: Results Of Preclinical Datasupporting
confidence: 74%
“…The prognostic role of microvessel density in squamous cell carcinoma of the upper aerodigestive tract was also confirmed by other studies which reported a higher density for more advanced stages [4]. …”
Section: Introductionsupporting
confidence: 71%
“…The relationship between MVD and prognostic parameters in head and neck epidermoid carcinoma could not be completely explained [20]. In spite of studies finding a relationship between high MVD and tumor progression, tumor stage and grade, studies suggesting that there was no such relationship have also been reported [7,8,12,20-22].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of studies finding a relationship between high MVD and tumor progression, tumor stage and grade, studies suggesting that there was no such relationship have also been reported [7,8,12,20-22]. Tse et al [19] conducted a study on 186 cases with head and neck epidermoid carcinomas including 34 cases with laryngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%